Model Pembelajaran Kooperatif Tipe Scramble dalam Meningkatkan Motivasi Belajar Siswa - Iis Aisyah; Cucun Nurazizah; Suharyanto H. Soro; Ida Tejawiani (Global Education Journal, 2026)
Learning motivation is one of the important factors that determine the success of the learning process at the elementary school level. Low student learning motivation is one of the gaps in optimizing the achievement of learning objectives. One alternative learning model that is considered capable of increasing learning motivation is the Scramble type cooperative learning model which emphasizes group activities through the arrangement of randomized answers so as to encourage active student involvement. This study aims to describe the Scramble type cooperative learning model in increasing student learning motivation. The study used a case study approach. Data collection methods through observation, in-depth interviews, and documentation studies, then analyzed using the interactive model of Miles, Huberman, and Saldaña through data reduction, data presentation, and drawing conclusions. The results of the study indicate that (1) The implementation of the Scramble type cooperative learning model is able to create an active, collaborative, and enjoyable learning atmosphere so that it motivates student learning; (2) Increased motivation is shown through increased student participation in discussions, courage to express opinions, cooperation between students, and enthusiasm in participating in learning. The conclusion of this study is that the Scramble type cooperative learning model can increase student learning motivation.